EFEKTIVITAS BUKU SAKU DAN PERAN TEMAN SEBAYA DALAM MENINGKATKAN KESEHATAN REPRODUKSI REMAJA - Bansu, Istiana Asrari (Jurnal Ilmu Kebidanan, 2025)
Biological and sociological changes in adolescents allow for two forms of integration. First, they form a sense of consistency in their lives. Second, the achievement of the established role. Juvenile delinquency occurs because adolescents fail to reach the second integration period. Various emotional turmoil arises and can affect adolescent health. The role of the closest person is like a double-edged sword, which can be the reason for the success of adolescents in maintaining and preserving their reproductive health. This study aimed to see the pocketbook method's effectiveness and peers' role in improving students' reproductive health. This study used a one-group pre-posttest design. The pocketbook method is effective, with a calculated t value for knowledge and attitudes of 6.294> t table 2.201, which means that there is a difference in the average knowledge and attitude, or the application of the pocketbook method results in changes in knowledge and attitudes. The role of peers is influential, with a calculated t value of 7.345 > t table 2.201, which means that there is a difference in the average knowledge and attitude, or the application of the peer method results in changes in knowledge and attitudes.